Helium range viability for online range probing in mixed carbon-helium beams - Hardt, Jennifer; Pryanichnikov, Alexander A.; Jäkel, Oliver; Seco, Joao; Wahl, Niklas (Medical physics, 2025)
Background: Recently, mixed carbon-helium beams were proposed for range verification in carbon ion therapy: helium, with three times the range of carbon, serves as an online range probe and is mixed into a therapeutic carbon beam. Purpose: Treatment monitoring is of special interest for lung cancer therapy; however, the helium range might not always be sufficient to exit the patient distally. Therefore, mixed beam use cases of several patient sites are considered. Methods: An extension to the open-source planning toolkit, matRad, allows for calculation and optimization of mixed beam treatment plans. The use of the mixed beam method in 15 patients with lung cancer, as well as in a prostate and liver case, for various potential beam configurations was investigated. Planning strategies to optimize the residual helium range considering the sensitive energy range of the imaging detector were developed. A strategy involves adding helium to energies whose range is sufficient. Another one is to use range shifters to increase the beam energy and thus helium range. Results: In most patient cases, the residual helium range of at least one spot is too low. All investigated planning strategies can be used to ensure a high enough helium range while still keeping a low helium dose and a satisfactory total mixed carbon-helium beam dose. The use of range shifters allows for the detection of more spots. ConclusionThe mixed beam method shows promising results for online monitoring. The use of range shifters ensures a high enough helium range and more detectable spots, allowing for a wider-spread application.